Mental exercises according to the vital rhythm, its mental and physical cycle and its effect on learning some basic skills of basketball for high school students - Najat Baqir Mashkoor (physical education and sport sciences college for women/ Baghdad University, 2021)
The method of selecting exercises and preparing them is not sufficient if they do not coincide ith the method of teaching and a modern method of learning. To two experimental and equal groups, one of which implements the educational variable, which is mental exercises in the cycle of ental rhythm, and the second group in the cycle of physical rhythm, and the aim of this is to know hich of the rhythms is better in teaching skills through mental exercises and results have resulted C research that the group physical rhythm is the most important and best in the development of physical attributes, but the group rhythm in the mental cycle are better in basic skills basketball